Translanguaging Practices in Tertiary Education: A Focus on Types & Pedagogical Functions - Putu Agung Wawan Widyasastrena; Ni Made Ratminingsih; Putu Kerti Nitiasih (Universitas Pendidikan Ganesha, 2025)
Higher education institutions continue to face considerable challenges in accommodating students’ linguistic diversity and delivering complex learning materials in foreign languages. Limited foreign language proficiency often hinders students’ comprehension, while lecturers face difficulties in effectively explaining technical concepts in multilingual contexts. Rigid, single-language teaching approaches may further reduce the effectiveness of teaching and learning. This study aims to explore the types and functions of translanguaging practices implemented in a Technology for Teaching and Learning course. A qualitative research design was employed, with classroom observations conducted over ten sessions involving one lecturer and 23 students. Data were analyzed thematically using an established translanguaging categorization framework. The findings revealed seven out of eight identified types of translanguaging: Making Comparisons, Asking and Answering Questions, Explaining Concepts, Giving Directions, Making Observations, Agreeing, and Exclaiming, with affirming absent. Explaining Concepts emerged as the most dominant type, highlighting the role of translanguaging in clarifying technical terms and facilitating understanding of complex concepts. These practices served interpretive, managerial, and interactive functions and involved three languages: Indonesian, English, and Balinese. The study concludes that translanguaging holds strong potential as an inclusive and contextual pedagogical strategy, with implications for developing flexible multilingual learning models in higher education.